REVIEW OF DAWN OF GOLD by Philip Barton - Almeida Jorge, Pedro (REVISTA PROCESOS DE MERCADO, 2022)
In the present essay, we will start by providing an overview of Barton’s theory of money and of gold’s primacy in markets and civilization. Then, we will describe the historical claims made by the author in defense of his thesis and proceed to a review of the relevant literature, in order to assess the likelihood of his interpretation of historical facts.